Influence of Prey Size on the Capture of Social Wasps (Hymenoptera: Vespidae) by the Orb-Web Spider Nephilengys cruentata - Mendes, Lucas William; Netto, Jose Chaud [UNESP]; Barbieri, Eduardo Feltran [UNESP]; Guarda, Danilo Demarchi; Brochetto Braga, Marcia Regina [UNESP] (California State University, 2010)
The objective of the present study was to evaluate the plasticity of the hunting behavior of the spider Nephilengys cruentata (Araneae: Nephilidae) facing different species of social wasps. Considering that wasps can consume various species of spiders and that their poison can be used as defense against many predators, the effect of the corporal size of the prey was evaluated in the behavior of N. cruentata. Predation experiments were conducted using three species of social wasps of different sizes and the data registered in this research were compiled through annotations and filming of the hunting behavior of each spider, in relation to the offered prey. The results revealed that the size of the wasp and the sequential offer of prey change the hunting behavior of the spider, and prey of large size have high influence on this behavior.
Keywords: spiders as prey; Hymenoptera: Vespidae